Value relevance of balanced scorecard: Malaysian evidence / Mohd Halim Bin Kadri - Kadri, Mohd Halim (2012)
This thesis is aimed at investigating the value relevance of Balanced Scorecard (BSC) measures incremental to book value and earnings of Malaysian public listed firms. The objectives of the thesis are to investigate (a) whether book value and earnings are still value relevance; (b) whether BSC measures are value relevance; (c) whether firm specific characteristics influence the value relevance of BSC measures; (d) whether book value and earnings could predict future market price; and (e) whether BSC measures could predict future market price. The sample was selected from Malaysian firms that have been listed for more than 10 years. Using a six year data from 2003 - 2008, the sample size is 1899 firm-years for the analysis current year market price and 1467 firm-years for the analysis of future year market price. This thesis employed equity valuation models that are developed based on established and well accepted equity valuation models. The results reveal that book value and earnings are still value relevance in Malaysian market over a six year period under study to the extent that the coefficient of correlation of book value is stable. At the same time, the coefficient of earnings is in an increasing trend. All BSC metrics are value relevant to investors. The thesis also finds that firm specific characteristics influenced the composition of relevance BSC measures. It was further found that book value, earnings and BSC measures could predict future market price. The availability of BSC variables that suit all sectors is the main limitation of the study. The empirical results provide a concrete and practical framework for the use of BSC in valuation of firms. The model helps the management in monitoring firm performance and at the same time helps the investors in evaluating firm performance. The study is original with regards to methodology in which the sample is selected from Malaysia, a developing country, an inefficient market and not tested before. Unlike previous studies, all sectors are selected as sample except for banking due to its different setting and regulation. The valuation model also includes variables that are not tested previously in equity valuation.